Quality and Dose Optimized CT Trauma Protocol – Recommendation from a University Level-I Trauma Center - Kahn, Johannes; Kaul, David; Böning, Georg; Rotzinger, Roman; Freyhardt, Patrick; Schwabe, Philipp; Maurer, Martin H.; Renz, Diane Miriam; Streitparth, Florian (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2017)
Purpose As a supra-regional level-I trauma center, we evaluated computed tomography (CT) acquisitions of polytraumatized patients for quality and dose optimization purposes. Adapted statistical iterative reconstruction [(AS)IR] levels, tube voltage reduction as well as a split-bolus contrast agent (CA) protocol were applied.Materials and Methods 61 patients were split into 3 different groups that differed with respect to tube voltage (120 – 140 kVp) and level of applied ASIR reconstruction (ASIR 20 – 50 %). The CT protocol included a native acquisition of the head followed by a single contrast-enhanced acquisition of the whole body (64-MSCT). CA (350 mg/ml iodine) was administered as a split bolus injection of 100 ml (2 ml/s), 20 ml NaCl (1 ml/s), 60 ml (4 ml/s), 40 ml NaCl (4 ml/s) with a scan delay of 85 s to detect injuries of both the arterial system and parenchymal organs in a single acquisition. Both the quantitative (SNR/CNR) and qualitative (5-point Likert scale) image quality was evaluated in parenchymal organs that are often injured in trauma patients. Radiation exposure was assessed.Results The use of IR combined with a reduction of tube voltage resulted in good qualitative and quantitative image quality and a significant reduction in radiation exposure of more than 40 % (DLP 1087 vs. 647 mGyxcm). Image quality could be improved due to a dedicated protocol that included different levels of IR adapted to different slice thicknesses, kernels and the examined area for the evaluation of head, lung, body and bone injury patterns. In synopsis of our results, we recommend the implementation of a polytrauma protocol with a tube voltage of 120 kVp and the following IR levels: cCT 5mm: ASIR 20; cCT 0.625 mm: ASIR 40; lung 2.5 mm: ASIR 30, body 5 mm: ASIR 40; body 1.25 mm: ASIR 50; body 0.625 mm: ASIR 0.Conclusion A dedicated adaptation of the CT trauma protocol (level of reduction of tube voltage and of IR) according to the examined body region (head, lung, body, bone) combined with a split bolus CA injection protocol allows for a high-quality CT examination and a relevant reduction of radiation exposure in the examination of polytraumatized patientsKey Points Citation Format
Keywords: CT; contrast agents; trauma; CT spiral